Uji Dosis Pupuk Kandang Kambing Dan Macam Pupuk Majemuk Terhadap Pertumbuhan Dan Hasil Tanaman Kacang Tanah (Arachis Hypogaea L.) - Supriyadi, Teguh; Soemarah KD, Tyas; Suprapti, Endang; Budiyono, Agus (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2024)
The peanut plant (Arachis hypogaea L.) is a food crop that has a strategic role in the national economy and given its multipurpose function as a source of food, feed and industrial raw materials. The aim of this research was to determine the growth and yield of peanut plants by providing goat manure and various types of compound fertilizer. The research was carried out in August - December 2022 in Dukuh Pokoh, Musuk Village, Musuk District, Boyolali Regency with an altitude of 632 (masl) and the soil type is Vertisol (PPT = Grumosol). The research used the Factorial method with a basic design of Complete Randomized Block Design (RAKL) consisting of 2 treatment factors, The first factor was the dose of goat manure: D1: 5 tons/ha, D2: 10 tons/ha, D3: 15 tons/ha. The second factor is the type of compound fertilizer: M1: 15-15-15, M2: 16-16-16, M3: 30-6-8. The results of the study showed that (1) The treatment dose of goat manure (D) had a very real influence on the number of pods planted, the number of pods contained in the plant, the weight of 100 seeds and had no effect on plant height, weight of fresh stover, weight of dry stover, number of empty pods per plant, pod weight per plant and pod weight per plot. (2) The type of compound fertilizer (M) had a very significant effect on fresh stover weight, dry stover weight and pod weight per plot. Significant effect on pod weight per plant and weight of 100 seeds and no effect on plant height, number of pods per plant, number of filled pods per plant, and number of empty pods per plant. (3) The combination of doses of goat manure (D) and types of compound fertilizer (M) has a very significant effect on the weight of fresh stover and the weight of dry stover. Has a significant effect on the weight of 100 seeds and has no significant effect on plant height, number of pods per plant, number of filled pods per plant, number of empty pods per plant, weight of the pods per plant and weight of the pods per plot. (4) The best results were at a fertilizer dose of 15 tonnes/ha with 15-15-15 compound fertilizer, namely pod weight of 751.60 gr per plot (3.11 tonnes/ha of dry beans).